2008
DOI: 10.1002/masy.200851023
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Applications of Metal Complexes Binding to Biological Macromolecules

Abstract: Summary: Biological macromolecules present in living organisms, like proteins, DNA, have many metal-binding sites. As a consequence, coordination compounds can react with such cellular components, displaying possible toxic effects, or they also may have beneficial applications. So metal ions and compounds not only are essential for life in e.g. dioxygen transport, or biocatalysis, but they can also be used for controlled toxicity in medicinal applications. Well-known examples are the application of gold compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…Ruthenium arene anticancer complexes are being widely studied as potential alternatives to platinum chemotherapeutics, [1][2][3][4][5][6][7][8][9] especially because acquired resistance to platinum-based drugs represents a major clinical drawback for compounds such as cisplatin (CDDP) 10,11 and oxaliplatin (OXA). 12,13 This type of resistance usually develops as a consequence of impaired cellular accumulation that can be caused by lower cellular uptake or increased cellular efflux.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium arene anticancer complexes are being widely studied as potential alternatives to platinum chemotherapeutics, [1][2][3][4][5][6][7][8][9] especially because acquired resistance to platinum-based drugs represents a major clinical drawback for compounds such as cisplatin (CDDP) 10,11 and oxaliplatin (OXA). 12,13 This type of resistance usually develops as a consequence of impaired cellular accumulation that can be caused by lower cellular uptake or increased cellular efflux.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 assay showed that induction of apoptosis occurred in V79 379A and A549 cells via mitochondrial pathway ( Figure 5). Chemotherapy was based on apoptotic cell death mechanism and some cancer cells were killed by including Pt(II) and Au(III) compounds via apoptosis like cisplatin 32 . The results of researches about cancer have demonstrated, that these metal complexes are really appropriate drug materials for treatment of various cancer types because apoptosis and cytotoxicity are closely related with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we demonstrate the efficacy of Cu 2+ and Zn 2+ in promoting the solubility of CX5461 (Figure ), a first‐in‐class anticancer candidate. These metal ions are particularly appropriate to this method since: (i) they exhibit high ligand exchange rates, (ii) they are relatively non‐toxic biological species, and (iii) they allow comparison of redox‐inert (Zn 2+ ) and redox‐active (Cu 2+ ) metal ions …”
Section: Figurementioning
confidence: 99%
“…This addresses ak ey challenge in medicinal chemistry,w hich is the limiteda queous solubility of many promising pharmaceuticals. These metal ions are particularly appropriate to this method since:( i) they exhibit high ligand exchange rates, [4] (ii)they are relativelyn on-toxic biological species, [5] and (iii) they allow comparison of redox-inert (Zn 2 + )a nd redox-active (Cu 2 + )m etal ions. [3] Our approach is broadly applicable to hydrophobicm oleculesw ith common metal-coordinating groups, such as amines.…”
mentioning
confidence: 99%